The characteristics of aesthetic education in Islamic philosophy - Alashari, Duaa; Abdelaziz, Berghout (Usuli Faqih Research Centre PLT, 2024)
This research aims to identify the conceptions of aesthetic education from the Islamic viewpoint to expose the characteristics, purposes, and goals. This research employed a descriptive and analytical method that depended on gathering and evaluating facts and information to develop conclusions and accurately define the concepts of beauty from an Islamic perspective.The study reached several conclusions, among them the increased originality in aesthetic education in Islamic vision. A person's delicate senseand gentle feelings are developed due to aesthetic education, which helps him differentiate between the good and bad in his life. This is in addition to the role and importance of aesthetic education in forming and developing the human personality in all aspects.